2021
DOI: 10.1021/acs.nanolett.1c01244
|View full text |Cite
|
Sign up to set email alerts
|

A Broadband Photoelectronic Detector in a Silicon Nanopillar Array with High Detectivity Enhanced by a Monolayer Graphene

Abstract: To meet the fast-growing need for broad applications in remote sensing, novel optoelectronic devices with high detectivity in full bands and room temperature operation are urgently desired. This paper reports our progress in developing a specially designed photovoltaic detector by integrating a monolayer graphene onto a silicon-based nanopillar array standing on a p–n junction. Optoelectronic measurements of the fabricated detectors show that the monolayer graphene plays a critical role in device performance. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 43 publications
0
12
0
1
Order By: Relevance
“…In contrast, the EQE looks very flat from λ = ∼970 nm down to ∼400 nm because the decrease of R at the lower λ is compensated by the decrease of λ itself, as clearly seen in the EQE formula: EQE = ( hc / q ) (1/λ)­R, where h is the Planck constant and q is the electron charge. Especially, the EQE reaches ∼90% in the visible range (∼400 to ∼900 nm), much larger than those previously known for GR/Si-junction-based PDs, ,,,,,, as summarized in Table . In contrast, the R /EQE of the PD counterpart with pristine (undoped)-GR TCE showed a relatively low 0.34 A W –1 /71% at λ = 600 nm (Figure S5), respectively, because of the high sheet resistance (640 Ω/sq) of the pristine GR despite the perfect transmittance.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…In contrast, the EQE looks very flat from λ = ∼970 nm down to ∼400 nm because the decrease of R at the lower λ is compensated by the decrease of λ itself, as clearly seen in the EQE formula: EQE = ( hc / q ) (1/λ)­R, where h is the Planck constant and q is the electron charge. Especially, the EQE reaches ∼90% in the visible range (∼400 to ∼900 nm), much larger than those previously known for GR/Si-junction-based PDs, ,,,,,, as summarized in Table . In contrast, the R /EQE of the PD counterpart with pristine (undoped)-GR TCE showed a relatively low 0.34 A W –1 /71% at λ = 600 nm (Figure S5), respectively, because of the high sheet resistance (640 Ω/sq) of the pristine GR despite the perfect transmittance.…”
Section: Resultsmentioning
confidence: 76%
“…Nevertheless, the photoresponse is limited in its further enhancement owing to the large leakage current caused by relatively high-density defect states at the GR/Si interface . To overcome this problem, many researchers have made a lot of efforts to improve the performance by giving varieties to the basic structure of the GR/Si heterojunction. Si quantum dots (SiQDs)-embedded SiO 2 (SiQDs:SiO 2 ) has been highly attractive for photonic device applications, thanks to distinctive properties such as stronger light absorption and faster photo-sensing than bulk Si. Particularly, SiQDs:SiO 2 was well applied in solar cells and PDs. The optoelectronic properties of the GR/Si heterojunction proved to be improved by employing SiQDs:SiO 2 between GR and a Si wafer in previous studies, , resulting from the improvement of the band profiles at the GR/Si interface.…”
Section: Introductionmentioning
confidence: 99%
“…Within this framework, the low processing cost and the ease of integration have inspired the development of various self-biased Si heterojunctions with high performance. [1][2][3][4][5][6] However, the simply constructed heterojunction silicon photodiodes invariably exhibit an external quantum efficiency (EQE) significantly below 100%. [7][8][9][10] The advent of black silicon (b-Si) has led to the development of innovative photodiodes and solar cells that yield high quantum efficiency over a broadband of wavelengths, having elegant combinations of advanced surface passivation technologies, light trapping/antireflection structures, and device constructs.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, various alternative strategies have drawn recent research focus toward the development of a single contact material that can be simply integrated within nanostructured Si morphology to achieve high quantum efficiency heterojunctions. [4,[18][19][20][21] For example, Liang et al, reported a selfbiased poly (3,4-ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS)/Si nanowire photodetector with 60-80% EQE from 400 to 900 nm. [21] Notwithstanding these reported advances, present-day heterojunction photodetectors continue to fall short of achieving unity EQE across the visible and nearinfrared (NIR) wavelengths due to nonideal absorption, nonoptimal charge carrier transport, photocarrier recombination losses in bulk and at interfaces, severe parasitic optical absorption in various contact layers and more.…”
Section: Introductionmentioning
confidence: 99%
“…12 A graphene/Si nanopillar array exhibited a broadband detection in 450-1100 nm with photovoltaic responsivity of B106 V W À1 at 860 nm. 13 Moreover, a PdSe 2 /Si nanowire array exhibited an ultrabroad spectrum response range of 0.2-4.6 mm with a high responsivity of 726 mA W À1 . 14 According to the reported results, silicon-based broadband detectors are mainly realized by combining two dimensional materials to make heterojunction detectors, which have the problems of instability and low responsivity.…”
Section: Introductionmentioning
confidence: 99%